용사 코팅한 ZrO2/W/Mo-Graphite 코팅층의 2100 ℃ 열처리 후 미세조직 변화에 관한 연구 - 안규백; Gyu Baek Ahn; 최경환; Kyeong Hwan Choe; 김상섭; Sang Sub Kim; 조규섭; Gue Serb Cho (대한금속·재료학회지, 54(8), 2016)
A tungsten coating was deposited onto a graphite substrate using the atmospheric plasma spraying (APS) technique. In order to increase the adhesion strength between the metallic tungsten(W) and graphite, a molybdenum (Mo) interlayer was pre-deposited onto the graphite surface by utilizing the APS technique. Also, after deposition of a APS-W coating, a zirconia (ZrO2) was deposited onto the W coating layer. For the APS process, argon and helium were used as the plasma-forming gases, and argon was used as the shield gas to protect the plasma from oxidation. After the APS coating process, heat exposure treatment was performed at 2100 ℃ for 360 h within a sapphire single crystal-growing furnace in order to evaluate the thermal stability of the coatings. After heat treatment, the ZrO2/W/Mo coating layers were bound with the graphite without any peeling off. The microvickers hardness of the APS-W coating layer was increased after heat treatment due to the formation of carbides. Also, carbide phases such as Mo2C, WC, ZrC and Mo3C2 were identified by XRD diffraction and EDS analysis, by analyzing the depths below the coating surface. It was considered that the Mo interlayer served as a good buffer layer between the APS-W coating and the graphite after the heat exposure treatment because the lattice structure of the molybdenum carbide was similar to that of the graphite. (Received September 16, 2015; Accepted Mach 11, 2016)